2013 IEEE International Conference on Acoustics, Speech and Signal Processing 2013
DOI: 10.1109/icassp.2013.6639025
|View full text |Cite
|
Sign up to set email alerts
|

A new mask-based objective measure for predicting the intelligibility of binary masked speech

Abstract: Mask-based objective speech-intelligibility measures have been successfully proposed for evaluating the performance of binary masking algorithms. These objective measures were computed directly by comparing the estimated binary mask against the ground truth ideal binary mask (IdBM). Most of these objective measures, however, assign equal weight to all time-frequency (T-F) units. In this study, we propose to improve the existing mask-based objective measures by weighting each T-F unit according to its target or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…However, a number of studies have shown that each T-F unit has a different perceptual effect depending on its intensity (Zhang et al, 2001;Yu et al, 2013) as well as different acoustic correlates Allen, 2009, 2011). To the best of our knowledge, no studies have yet assessed the relative contribution of individual T-F units to speech intelligibility in the context of speech separation in noise.…”
Section: Introductionmentioning
confidence: 99%
“…However, a number of studies have shown that each T-F unit has a different perceptual effect depending on its intensity (Zhang et al, 2001;Yu et al, 2013) as well as different acoustic correlates Allen, 2009, 2011). To the best of our knowledge, no studies have yet assessed the relative contribution of individual T-F units to speech intelligibility in the context of speech separation in noise.…”
Section: Introductionmentioning
confidence: 99%